46, XY disorder of sex development due to 17-beta hydroxysteroid dehydrogenase type 3 deficiency: a plea for timely genetic testing. (December 2016) - Grimbly, Chelsey; Caluseriu, Oana; Metcalfe, Peter; Jetha, Mary; Rosolowsky, Elizabeth
Abstract Background 17β-hydroxysteroid dehydrogenase type 3 (17βHSD3) deficiency is a rare cause of disorder of sex development (DSD) due to impaired conversion of androstenedione to testosterone. Traditionally, the diagnosis was determined by βHCG-stimulated ratios of testosterone:androstenedione < 0.8. Case presentation An otherwise phenotypically female infant presented with bilateral inguinal masses and a 46, XY karyotype. βHCG stimulation (1500 IU IM for 2 days) suggested 17βHSD3 deficiency although androstenedione was only minimally stimulated (4.5 nmol/L to 5.4 nmol/L). Expedient genetic testing for theHSD17B3 gene provided the unequivocal diagnosis. Conclusion We advocate for urgent genetic testing in rare causes of DSD as indeterminate hormone results can delay diagnosis and prolong intervention.